1996
DOI: 10.1074/jbc.271.42.25981
|View full text |Cite
|
Sign up to set email alerts
|

Complete Phenotypic Characterization of apobec-1 Knockout Mice with a Wild-type Genetic Background and a Human Apolipoprotein B Transgenic Background, and Restoration of Apolipoprotein B mRNA Editing by Somatic Gene Transfer of Apobec-1

Abstract: We have produced gene knockout mice by targeted disruption of the apobec-1 gene. As recently reported by Hirano et al. (Hirano, K.-I., Young, S. G., Farese, R. V., Jr., Ng, J., Sande, E., Warburton, C., Powell-Braxton, L. M., and Davidson, N. O. (1996) J. Biol. Chem. 271, 9887-9890), these animals do not edit apolipoprotein (apo) B mRNA or produce apoB-48. In this study we have performed a detailed analysis of the lipoprotein phenotypic effects of apobec-1 gene disruption that were not examined in the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 32 publications
5
68
1
Order By: Relevance
“…The cells were expanded to passage 14 and used to generate knockout mice as described previously (17). Three positive ES cell clones were injected into blastocysts of C57BL/6J, and chimeric mice were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were expanded to passage 14 and used to generate knockout mice as described previously (17). Three positive ES cell clones were injected into blastocysts of C57BL/6J, and chimeric mice were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed phenotypic data generated by the JAX KOMP2 pipeline and available from the International Mouse Phenotyping Consortium (IMPC; www.mousephenotype.org/) and found significant impacts on the immune and hematopoietic system as well as altered homeostasis and metabolism. While no specific role for APOBEC1 has been reported in either the immune or hematopoietic system, knockouts do have altered cholesterol metabolism (Nakamuta et al 1996).…”
Section: A1cf Has Novel Physiological Rolesmentioning
confidence: 99%
“…However, while global ablation of Apobec1 in a mouse model resulted in a complete loss of ApoB editing, there were no gross impacts on fecundity or fertility (Hirano et al 1996) and only moderate impacts on serum lipoprotein profiles (Nakamuta et al 1996). In contrast, while A1CF and APOBEC1 have very similar expression profiles in adult tissues, there was strong evidence that A1CF may have roles outside of C-to-U editing (Sowden et al 2002;Chester et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the apoB RNAs from 29 of the 30 species were good substrates for APOBEC-1 and were edited between 33 and 59% by the rabbit APOBEC-1. Previously, it has been shown that rat and mouse apoB mRNA are good substrates for APOBEC-1, in vitro and in vivo, respectively (2,28,(32)(33)(34). However, the ApoB mRNA from one of those species, the guinea pig, was edited poorly (3%).…”
Section: Phylogeneticmentioning
confidence: 99%